Molecular mechanism of action of tetracycline-loaded calcium phosphate nanoparticle to kill multi-drug resistant bacteria - Nandi, Susmita; Chakrabarty, Soumajit; Bandopadhyay, Pathikrit; Mandal, Dipanwita; Azaharuddin, Md; Das, Abhijit; Pal, Anabadya; Ghosh, Sourav; Nandy, Sanchita; Sett, Upasana; Basu, Tarakdas (Biochimica et biophysica acta. General subjects, 2025)
In earlier communications we reported about nanonization of the antibiotic tetracycline (Tet) by entrapping it within the biocompatible and highly membrane penetrating nano-carrier molecule – calcium phosphate nanoparticle (CPNP). The synthesized Tet-CPNP killed different Tet-resistant bacteria in vitro as well as in vivo (in mice). Moreover, such nanonized tetracycline had bactericidal mode of action, in contrast to bacteriostatic mode of action of bulk tetracycline. The present study unveils the molecular mechanism of action of Tet-CPNP. This study was conducted to investigate the mode of interaction of Tet-CPNP/Tet with intact 70S bacterial ribosome by the techniques of spectrophotometry, spectrofluorimetry, circular dichroism, gel electrophoresis and transmission electron microscopy. Experimental observations revealed that (i) binding affinity of Tet-CPNP was higher than that of only tetracycline with ribosome and (ii) binding of Tet-CPNP, but not of tetracycline, loosened ribosome conformation, finally disrupting and degrading ribosome. Bactericidal action of Tet-CPNP was rooted from degradation of cellular ribosomes and thereby blockage of protein translation phenomenon. Therefore, the problem of obsolescence of tetracycline, a cheap, first-generation, broad-spectrum antibiotic, due to generation of huge tetracycline-resistant bacteria, can be removed by the Tet-CPNP. [Display omitted] •Development of nanonized tetracycline to kill MDR bacteria.•The nanoform of tetracycline shows irreversible bactericidal action.•The bulk tetracycline has reversible bacteriostatic action.•Binding affinity of nano-tet to ribosome is higher than bulk tet.•Nanonized tetracycline, but not free tetracycline, degrades bacterial ribosome.